Exploring the Work-Life Experiences of Temporary Employment Service Employees in South Africa - Marule, Thabang E.; Schurink, Willem J.S.; Ukpere, Wilfred I. (Journal of Reviews on Global Economics, 2019)
This study examines the working career experience of temporary employment services' (TES) employees within a globalised economic environment. Incorporating the ethical framework for human resources and industrial relations (HRIR), the study investigates the perceptions of serving and ex-temporary employment services (TES) employees in relation to their work and career experiences. A multiple case study was adopted, with a focus on selected retail, banking, telecommunications, hospitality and Public Service. The finding reflected some mixed reactions for work experience and career outcomes and provided some platform for gaining experience by making informed career choices on one hand and addressing the poor conditions of work on the other. It was further established that the overall perceptions held about TES employment practices may fall below the HRIR ethical norms. This paper offers management and policy makers an insight into the mechanics of the TES phenomenon in the context of the HRIR ethics.